Efektivitas Snack Biscoke (Biskuit Coklat Daun Kelor) terhadap Status Anemia Pada Remaja Putri - Anik Sulistiyanti; Adisti Amalya Putri Handayani; Fatimah Eira Yudhayana (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Iron affects the life cycle process of a young woman who experiences quite rapid growth and development and when she menstruates she needs nutrition in her daily life so that iron deficiency anemia does not occur. Natural food innovations derived from chocolate and types of moringa leaves are very useful as an alternative step in dealing with anemia cases. Objective: To determine the effectiveness of Biscoke snacks (moringa leaf chocolate biscuits) on the anemia status of young women in Wirengan Masaran Village, Sragen in 2024. The research method used is quantitatively a Quasy Experiment type with a pre-test and post-test design with a control group design in one intervention group and 30 respondents with anemia as a research sample, namely purposive sampling. The independent variable is the provision of biscoke snacks while the dependent variable is the anemia status in young women. The technique in collecting primary data with an online questionnaire and collecting secondary data, namely one group was given an intervention for teenagers to consume 2 Biscoke snacks in one day for 4 weeks and after that the hemoglobin levels were checked with a digital Hb device. The study used two methods with univariate analysis and bivariate analysis where the statistical test was paired t-test. Processing with SPSS ver.25 test tool. Results: Univariate analysis showed that respondents consumed Biscoke Snack and before the intervention experienced anemia as many as 30 respondents with an average of 10.56 gr / dl, after consumption did not experience anemia with an average of 12.80 gr / dl. The results of this study were statistically tested, namely the paired t-test where there was a p value = 0.000<0.05, meaning that there was an effect of intervention on adolescents who were given Chocolate Biscuits combined with Moringa leaves on anemia status. Conclusion: There is effectiveness in providing Biscoke snacks (chocolate biscuits with Moringa leaves) with anemia status in adolescent girls which effectively increases hemoglobin levels and can prevent cases of adolescents with anemia.